Does CMMI Implementation affect the Performance of the Firm? An Evaluation from a Dynamic Capabilities Approach - Eduardo Agenjo; Natalia Martín-Cruz; Cristina Ruiz-Martin; Adolfo López-Paredes (International Journal of Production Management and Engineering)
In this paper, we study the impact of the Capability Maturity Model Integration (CMMI) on firm performance both during and after its implementation. The literature pointed out that CMMI is theoretically related to the generation of dynamic capabilities. To give an empirical view of these theories, we built a database of economic and financial data from Spanish firms involved in programming, consultancy or another computer-related sector. This data allowed us to study the relationship between the use of CMMI and the firm economic and financial performance in an empirical way. The main finding of the analysis is a negative relationship between the use of CMMI and profitability in the firms during the analyzed period and sector.